PENGARUH TAX AVOIDANCE DAN STRUKTUR KEPEMILIKAN TERHADAP TIMELINESS PUBLIKASI LAPORAN KEUANGAN DI BURSA EFEK INDONESIA - Belya Dwi Puteri; Made Dudy Satyawan (JURNAL AKUNTANSI DAN AUDITING, 2019)
The characteristics of financial statements in the form on the timeliness of financial statements publication is one of the requirements for information from financial statements to be relevant for the user’s decision. This study aims to determine the effect of tax avoidance and ownership structure on the timeliness of financial statement publication listed on the Indonesia Stock Exchange in period 2014-2018. Sample of research from purposive sampling is 475 companies with logistic regression analysis. The analysis evidence that tax avoindace, ownership concentrated on the family, and foreign ownership has an influence on the timeliness of financial statement publication. However, institutional ownership does not affect on the timeliness of financial statements publication.